1996
DOI: 10.1093/molehr/2.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of sperm function: A role for diacylglycerol in human sperm acrosomal exocytosis

Abstract: Using human spermatozoa stimulated with either progesterone or the Ca2+ ionophore A23187 to undergo acrosomal exocytosis, we have investigated potential pathways for generation of diacylglycerol (DAG) and have examined the possibility that DAG plays an important role in the exocytotic response. Both treatments resulted in rapid and considerable generation of DAG, followed by a limited rise in phosphatidic acid (PA). Further experiments indicated that phospholipase C (PLC) activity is important in this generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Indeed, the increase in cAMP concentrations following P stimulation is very low (Parinaud and Milhet, 1996), raising doubts about the relevance of the pathway in the response to the steroid. A similar situation applies for the phospholipase C/inositol3phosphate/diacylglycerol/protein kinase (PLC/IP3/DAG/PKC) pathway: although the enhancing effect of P on inositol trisphophate (Thomas and Meizel, 1989) and diacylglycerol (O'Toole et al, 1996a) synthesis has been reported, blockers of phospholipase C do not appear to affect P-stimulated Ca 2+ fluxes (Harper et al, 2004), and whether the pathway is involved in the induction of AR remains controversial (O'Toole et al, 1996b;Bonaccorsi et al, 1998). P at micromolar concentrations has been also shown to promote tyrosine phosphorylation of sperm proteins (Tesarik et al, 1993;Luconi et al, 1995) and this pathway is involved in AR and Ca 2+ influx in response to the steroid (Martinez et al, 1999;Bonaccorsi et al, 1995).…”
Section: P-induced Acrosome Reactionmentioning
confidence: 98%
“…Indeed, the increase in cAMP concentrations following P stimulation is very low (Parinaud and Milhet, 1996), raising doubts about the relevance of the pathway in the response to the steroid. A similar situation applies for the phospholipase C/inositol3phosphate/diacylglycerol/protein kinase (PLC/IP3/DAG/PKC) pathway: although the enhancing effect of P on inositol trisphophate (Thomas and Meizel, 1989) and diacylglycerol (O'Toole et al, 1996a) synthesis has been reported, blockers of phospholipase C do not appear to affect P-stimulated Ca 2+ fluxes (Harper et al, 2004), and whether the pathway is involved in the induction of AR remains controversial (O'Toole et al, 1996b;Bonaccorsi et al, 1998). P at micromolar concentrations has been also shown to promote tyrosine phosphorylation of sperm proteins (Tesarik et al, 1993;Luconi et al, 1995) and this pathway is involved in AR and Ca 2+ influx in response to the steroid (Martinez et al, 1999;Bonaccorsi et al, 1995).…”
Section: P-induced Acrosome Reactionmentioning
confidence: 98%
“…This leads to phospholipase C (PLC) activation which converts phosphatidyl inositol bisphosphate to diacylglycerol and inositol trisphosphate (O'Toole et al, 1996). The latter is involved in sperm capacitation and AR (Breitbart and Spungin, 1997).…”
Section: © European Society Of Human Reproduction and Embryologymentioning
confidence: 99%
“…Treatment with these agonists, including A23187/Ca 2+, results in a rapid generation of diacylglycerol (DAG) due to the hydrolysis of polyphosphoinositides by phosphoinositidase C [3,[6][7][8] and hydrolysis of phosphatidylcholine by a specific phospholipase C [3,8,9]. No evidence for the participation of the phospholipase D/phosphatidic acid phosphohydrolase pathway in the generation of DAG has been found [3].…”
Section: Introductionmentioning
confidence: 99%